How Poverty Shapes Caring for a Disabled Child: A Narrative Literature Review. (22nd August 2017) - van der Mark, Elise J.; Conradie, Ina; Dedding, Christine W.M.; Broerse, Jacqueline E.W.
Abstract: Despite ample research on the relationship between disability and poverty, the experiences of parents of disabled children are herein generally overlooked. We argue that an understanding of how poverty shapes caring for a disabled child is crucial for disability inclusive development. Therefore, this paper narratively reviews literature on carers of disabled children from various contexts published between 1995 and 2015. It uncovers a significant knowledge gap on the impact of poverty despite slowly emerging evidence on how political, cultural and socioeconomic exclusion stifles parents to enhance their families' wellbeing and possibly reap the benefits of development policies. Implications for future research are addressed. Copyright © 2017 John Wiley & Sons, Ltd.